Simultaneous optimization of curvature and curvature variation for tool path generation in high-speed milling of corners - Yang, Xuefeng; You, Youpeng; Yang, Wen-An (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2022)
The machining corners are an important feature of aircraft structure components. In the process of high-speed milling of the corner, the discontinuity of tangential direction and curvature of the tool path can lead to frequent starting and stopping of speed, sharp change of cutting force and feed direction, which will result in violent vibration of the machining tool, and ultimately affect the efficiency and quality of part machining. Recently, it has been demonstrated that G 3 (i.e., the variation rate of curvature with continuity) tool path has the potential to improve the smoothness and reduce the mechanical vibration in the field of corner machining. This study presents a corner-looping milling strategy for optimizing the tool path smoothly based on the first generation of tool path. A multi-objective tool path optimization model subject to multiple constraints such as G 3 continuity, transition error and transition length is developed to simultaneously minimize the curvature variation of the tool path curve and the extreme value of curvature. Moreover, an upgraded teaching–learning-based optimization algorithm is used to effectively solve the optimal solution. Compared with that of previously published literature, the proposed method can effectively improve the smoothness and maximum curvature of the corner tool path to avoid the sharp change of curvature. Experiment results show that the surface quality and the machining efficiency are improved.